The Antioxidant Activity of Combined Green Arabica Coffee Bean and Dahu Leaf Extract using DPPH Radical Scavenger Method - Zaman, Ridha Herwidia; Ismail, Sjarif; Khotimah, Siti (Jurnal Ilmu Kesehatan, 2022)
Coffee (Coffea arabica L.) and Dahu (Dracontomelon dao (Blanco) are combined to enrich the types of functional herbal drink with antioxidant properties. Dahu leaves and green coffee beans contain secondary metabolites with antioxidant properties. This research aims to investigate the interaction between the ethanolic extract of coffee (CA) and dahu (DD) and its effect on their antioxidant activity. The antioxidant activity test was performed using DPPH radical scavenging method on 2 control groups and 5 treatment groups, consisting of the CA sample group, the DD sample group, and 3 coffee and dahu (CA: DD) combination groups with different ratios. The research showed that antioxidant activities (%), expressed in mean ± SEM, for the control, DD, CA, CA:DD (1:1), CA:DD (3:1), and CA:DD (9:1) were (80.1 ± 0.4), (65.3 ± 1.5), (37.4 ± 2.4), (47.3 ± 0.4), (34.0 ± 1.4) and (33.4 ± 1.1) respectively. The coffee and dahu combination groups had lower antioxidant activities than single dahu extract, thus indicating an antagonistic interaction between coffee and dahu extracts.